Comparative Genomics of the First and Complete Genome of "Actinobacillus porcitonsillarum" Supports the Novel Species Hypothesis. (30th September 2018) - Donà, Valentina; Perreten, Vincent
Abstract : " Actinobacillus porcitonsillarum " is considered a nonpathogenic member of the Pasteurellaceae family, which phenotypically resembles the pathogen Actinobacillus pleuropneumoniae . Previous studies suggested that " A. porcitonsillarum " may represent a new species closely related to Actinobacillus minor, yet no full genome has been sequenced so far. We implemented the Oxford Nanopore and Illumina sequencing technologies to obtain the highly accurate and complete genome sequence of the " A. porcitonsillarum " strain 9953L55. After validating our de novo assembly strategy by comparing the A. pleuropneumoniae S4074 T genome sequence obtained by Oxford Nanopore Technology combined with Illumina reads with a PacBio-sequenced S4074 T genome from the NCBI database, we performed comparative analyses of the 9953L55 genome with the A. minor type strain NM305 T, A. minor strain 202, and A. pleuropneumoniae S4074 T . The 2, 263, 191 bp circular genome of 9953L55 consisted of 2168 and 2033 predicted genes and proteins, respectively. The lipopolysaccharide cluster resembled the genetic organization of A. pleuropneumoniae serotypes 1, 9, and 11, possibly explaining the positive reactions observed previously in serotyping tests. In contrast to NM305 T, we confirmed the presence of a complete apxIICABD operon in 9953L55 and 202 accounting for their hemolytic phenotype and Christie-Atkins-Munch-Petersen (CAMP) reaction positivity. Orthologous gene cluster analysis provided insight into the differential ability of strains of the A. minor /" porcitonsillarum " complex and A. pleuropneumoniae to ferment lactose, raffinose, trehalose, and mannitol. The four strains showed distinct and shared transposable elements, CRISPR/Cas systems, and integrated prophages. Genome comparisons based on average nucleotide identity and in silico DNA-DNA hybridization confirmed the close relationship among strains belonging to the A. minor /" porcitonsillarum " complex compared to other Actinobacillus spp., but also suggested that 9953L55 and 202 belong to the same novel species closely related to A. minor, namely, " A. porcitonsillarum ." Recognition of the taxon as a separate species would improve diagnostics and control strategies of pig pleuropneumonia.